Pengembangan Media Pendidikan Akupresur dan Pijat Oksitosin Pada Mahasiswa Poltekkes Jambi Jurusan Kebidanan - Pauline Kusmaryati; Netti Herawati; Ajeng Galuh Galuh Wuryandari (NHM PRESS, 2022)
One type of traditional health services that can be integrated in the public health center is acupressure. Acupressure to increase the amount of breast milk can be massaged at the intersection of the perpendicular line from the corner of the little finger nail. Oxytocin massage is one solution to overcome the inability to produce breast milk. The purpose of this study was to develop educational media for acupressure and oxytocin massage for Jambi Health Polytechnic students, Midwifery Department. This research uses research and development (R and D) methods. This research was conducted at the Jambi Health Polytechnic Department of Midwifery from May to November 2022. The population in this study were students at the Jambi Health Polytechnic Department of Midwifery. Samples were selected using the Purposive Sampling technique. Data analysis in this study used qualitative and descriptive quantitative analysis techniques. Overall according to media needs by material experts is 97% with a very decent category. Results based on media experts earned a prize rate of 83% in the eligible category. There is a significant difference (p value 0.000) from the students' prior knowledge before the intervention was given. The result of the percentage of respondents' responses to the media is 89.1% with a very good category. For further research, it is expected to be able to develop video media with interactive multimedia to determine the effect on students' practical skills. This video media of acupressure and oxytocin massage can be used in the teaching and learning process in the classroom.